DEVELOPMENT OF ARCHIVES MANUALLY IN THE UNIT SIMPAN PINJAM KOPERASI INTI BANDUNG - Robintang Yuni Andriyani; Yayan Firmansyah (Ebiz Prima Nusa, 2022)
Unit Simpan Pinjam Koperasi INTI, a subsidiary of PT Industri Telekomunikasi Indonesia (Persero) is a part of a cooperative that plays an important role in the savings and loan cooperative activities of employees of PT Industri Telekomunikasi Indonesia. The development of the Koperasi INTI with improved services makes the Unit Simpan Pinjam work optimally. Each activity of the Savings and Loans Unit produces information or data that is stored as a company archive, the information will be temporarily collected which will then be recapitulated and will be bound at the end of the year period, the binding is carried out based on the archive year, archive classification, and month. The Unit Simpan Pinjam has 5 (five) archive classifications, namely Commercial Banks, Incoming Banks, Outgoing Banks, Incoming Cash, and Outgoing Cash. The archival principle used in this archival project is a mixed principle, that is, each unit has its own storage area for each unit and at the end of the year period is stored in the cooperative's final storage area in one warehouse that is united with each cooperative unit. After binding the archives, the archives are moved to the warehouse to be stored and arranged based on a chronological storage system for the archive year and an alphabetical storage system for archive classification, namely Commercial Banks, Incoming Banks, Outgoing Banks, Incoming Cash, and Cash Out. After that, the guide's description was affixed to the filing cabinet and the table of contents was attached to the cupboard and warehouse door.